An alternative simulation budget allocation scheme for efficient simulation. (2nd June 2005) - Chen, Chun-Hung; Yucesan, Enver
We present an alternative simulation run allocation scheme for maximising efficiency in simulation experiments for decision making under uncertainty. The issue of simulation efficiency is addressed from two perspectives: we want to minimise the total computation cost, with a constraint that the overall simulation quality must be higher than a desired level; we would like to maximise the simulation quality with the constraint that the total computation cost can not exceed a given budget. While these two problems look different, we show that the solutions to these two problems are identical. Comparisons with other procedures show that our approach can achieve a speedup factor of 3∼4 for a 10-design example. The speedup factor is even higher for problems having a larger number of designs.